Developing Bilingual Learning Multimedia in Integral Application Learning Material For Vocational School - Rahim, Abdul; Hamdi, Syukrul; Arcana, I Nyoman (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
ICT advancement can be utilized to improve the quality of education. In this globalization era, the millennial generation is demanded to be technology literate and fluent in English to compete in the global world considering that English has been established as an international language. Therefore, the integration of English into learning in the form of multimedia bilingual learning is needed. This study aimed to determine the feasibility, attractiveness, and effectiveness of bilingual learning multimedia on the integral application material for vocational schools. This research is research and development. Based on the results of validation and field trials, the developed bilingual mathematics learning media was in the feasible, interesting, and effective categories. The feasibility of the bilingual learning multimedia based on the material expert validation obtained an average of 4.6 and the media expert validation obtained an average of 4.9 which indicated that the developed product was in the feasible category. The attractiveness of bilingual mathematics learning multimedia based on students’ responses was 89% in the very interesting category. The effectiveness of the developed bilingual learning multimedia to improve students' mathematics learning outcomes was known based on the N-Gain value of 0.8 in the high category.